Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1513/annalsats.201504-253oc
|View full text |Cite
|
Sign up to set email alerts
|

Prior Advance Care Planning Is Associated with Less Decisional Conflict among Surrogates for Critically Ill Patients

Abstract: Rationale: Although numerous studies have documented that family members in intensive care units struggle with end-of-life decisions for incapacitated patients, there is little information about whether prior advance care planning lessens the burden of decision making.Objectives: We sought to measure decisional conflict in surrogates of critically ill patients and to examine whether prior advance care planning is associated with less decisional conflict. Methods:We performed a secondary data analysis of a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 29 publications
6
74
0
Order By: Relevance
“…In this regard, predictors of decisional conflict identified in this study would provide useful guidance to develop interventions for family surrogates' end-of-life cancer decision-making. The strongest predictor of decisional conflict was whether or not family surrogates knew the patients' wishes about end-of-life treatments, which is consistent with a previous study that showed surrogates who had engaged in prior advance care planning conversations showed less decisional conflict (Chiarchiaro et al, 2015). This finding showed that family surrogates' decisional conflict could be effectively alleviated when patients and their surrogates communicated patients' wishes about end-of-life treatment before facing the terminal stage of cancer.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this regard, predictors of decisional conflict identified in this study would provide useful guidance to develop interventions for family surrogates' end-of-life cancer decision-making. The strongest predictor of decisional conflict was whether or not family surrogates knew the patients' wishes about end-of-life treatments, which is consistent with a previous study that showed surrogates who had engaged in prior advance care planning conversations showed less decisional conflict (Chiarchiaro et al, 2015). This finding showed that family surrogates' decisional conflict could be effectively alleviated when patients and their surrogates communicated patients' wishes about end-of-life treatment before facing the terminal stage of cancer.…”
Section: Discussionsupporting
confidence: 86%
“…It was also higher than that of surrogates in the USA who made endof-life decisions for critically ill patients in ICU (21.5; 25.5/100) (Chiarchiaro et al, 2015;Miller et al, 2016). While it has been a cultural tradition in Korean society for family members to take responsibility for making decisions on behalf of patients (Lee et al, 2013), our findings show that family members were unprepared to make end-oflife decisions, whereupon they experienced a severe level of conflict and stress in making decisions regarding end-of-life treatment for cancer.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…On the other hand, when patient goals and priorities are clearly established, patients may have better outcomes . For example, earlier conversations about patient goals and priorities in serious illness can lead to realistic expectations of treatment, enhanced goal‐concordant care, improved quality of life, higher patient satisfaction, more and earlier hospice care, fewer hospitalizations, better patient and family coping, reduced burden of decision making for families, and improved bereavement outcomes …”
mentioning
confidence: 99%